Pengaruh Edukasi Mencintai Diri Sendiri terhadap Tingkat Kepercayaan Diri Mahasiswa di Universitas Yatsi Madani 2025 - Ripqotun nissah; Ida Faridah; AYG Wibisono (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
Self-confidence is a crucial psychological factor that supports academic, social, and emotional development among university students. Low self-confidence is often associated with anxiety, stress, and adjustment difficulties in higher education settings. Recently, educational approaches based on self-love have gained attention as effective strategies to enhance students’ self-confidence. The concept of self-love involves self-acceptance, appreciation of one’s own existence, and fostering a positive attitude towards oneself without reliance on external validation. This study is a literature review aimed at analyzing and synthesizing empirical findings from ten previous studies investigating the influence of self-love education on students’ self-confidence. The data sources consist of relevant national and international journals published within the last five years. The analysis examines research design, intervention methods, and findings from each study. The results consistently indicate that self-love education, especially delivered through reflective modules and affirmative techniques, significantly improves students’ self-confidence. This approach effectively strengthens positive self-perception, reduces social anxiety, and enhances psychological resilience. The reviewed literature also emphasizes the importance of integrating self-love-based educational programs into university curricula as part of sustainable mental health strategies.